دور اللاتانوبروست في علاج الزرق مفتوح الزاوية لدى عينة من الساحل السوري - تعتاع عبد القادر; كردغلي نجوى; محمد مهى (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة /45/ مريضاً (62 عيناٌ) مصاب بالزرق البدئي مفتوح الزاوية. راجعوا العيادة العينية لمشفى الأسد الجامعي باللاذقية بين عامي 2005-2006 توزعوا بين ذكور 53% وإناث 47%. استخدمنا في دراستنا اللاتانوبروست لعلاج مرضى الزرق البدئي مفتوح الزاوية. لوحظ زيادة نسبة الإصابة مع تقدم العمر, فكانت أعلى نسبة للمرضى بين70-79 سنة بنسبة 31%. تقارب نسبة الإصابة بين الجنسين. في دراستنا كانت الإصابة الأحادية أكثر من الثنائية. حقق الدواء تخفيض ضغط العين IOP بمقدار 9.2 مم ز خلال عام واحد، بنسبة 34.49%. حقق 85.95% من المرضى ضغط عين ضمن الطبيعي. لم يستجب للمعالجة 9 عيون أي بنسبة 14.05%. الاختلاطات الملاحظة كانت متحملة من قبل المرضى ولم يوقف أي مريض العلاج. تمت التوصية باعتماد اللاتانوبروست كخط أول في العلاج الدوائي للزرق. 10. عدم اللجوء للجراحة قبل إعطاء المريض كل فرص العلاج الدوائي. The study was applied to 45 patients (62 eyes) with primary open angle glaucoma, who visited ophthalmic clinic at Al-Assad University Hospital (Lattakia) in the academic year 2005-2006. They were distributed as follows: ratio of males was 53% and females 47%. 1. In our study we used latanoprost to treat primary open angle glaucoma. 2. 31% of patients were between 70 and 79 years. 3. The disease between two sexes is approximately the same. 4. In our study, monolateral disease was noticed more thanbilateral disease. 5. Mean IOP reduction at one year was 9.2 mmHg, average was 34.49%. 6. 85.95% of patients achieved intraocular pressure within normal range. 7. 9 eyes did not respond to treatment: ratio was 14.05%. 8. Side effects were tolerated and none of the patients stopped the drug. 9. It was recommended to use latanoprost as a drug of first choice in medical treatment of primary open angle glaucoma. 10. Surgery is the last choice until we give patient all medical treatment chances.